Multi-colour beamsteering for optical wireless communications using spatial light modulators - Sangwongngam, P; Gomez, A; Quintana, C; Chun, H; Faulkner, G; O'Brien, D (IEEE, 2020)
This paper reports results from a single-hologram beamsteering system that uses multi-plane hologram generation to allow simultaneous beamsteering of the red and green components of white light. Gigabit-per-second transmission is demonstrated using eyesafe levels of optical power.